2023
DOI: 10.1177/10760296231169514
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Solid Tumor Patients Complicated With Venous Thromboembolism: A 10-Year Retrospective Cross-Sectional Study Based on 1482 Cases

Abstract: The aim of this single-centre 10-year retrospective observational study was to evaluate the profile of Chinese cancerous patients complicated with venous thromboembolism (VTE) based on demographic features, clinical characteristics, and medication exposure. Consecutive 1482 patients with solid tumor complicated with VTE at a tertiary center between 2012 and 2021 were retrospectively enrolled. Data were collected on demographics, comorbidities, discharge diagnoses, laboratory examination data, treatment details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…CVCs play a key role in inpatient settings, where they provide reliable central venous access for medium to long-term intravenous drug therapy. Numerous studies [33,34] have shown a strong association between long-term CVC use and the risk of upper extremity deep vein thrombosis (UEDVT). Consistent with these ndings, our study also identi ed CVCs as a major contributor to UEDVT.…”
Section: Discussionmentioning
confidence: 99%
“…CVCs play a key role in inpatient settings, where they provide reliable central venous access for medium to long-term intravenous drug therapy. Numerous studies [33,34] have shown a strong association between long-term CVC use and the risk of upper extremity deep vein thrombosis (UEDVT). Consistent with these ndings, our study also identi ed CVCs as a major contributor to UEDVT.…”
Section: Discussionmentioning
confidence: 99%